Memory's orbit : film and culture, 1999-2000 - Natoli, Joseph P., 1943- (SUNY series in postmodern culture., 2003)
"Mixing memoir and cultural criticism, Memory's Orbit examines the intersections between a wide range of films and current events, finding its theme and orbiting narrative structure in the personal stories we live within and their relationship to the social and cultural order. Joseph Natoli covers such films as The Matrix, American Beauty, Fight Club, Eyes Wide Shut, and American History X, as well as such headline events as the death of John F. Kennedy, Jr., the dot-com boom, the WTO protests in Seattle, and Bush versus Gore, consistently identifying those aspects of the social order that have shaped his narrating frame. Eschewing theoretical exposition and jargon, Natoli performs postmodern critique, and this book continues his innovative work in the genre of cultural studies."--Jacket